Ortaokul öğrenci görüşlerine göre başarısızlığın nedenleri - Tuncer, Murat; Bahadır, Ferdi (My University, 2017)
The purpose of this research is to evaluate the reasons for underachievement of the secondary school students according to the students' opinions. The data of the study were collected with the help of the researchers' underachievement reasons questionnaire. One of the findings of the research is that students have difficulty in determining the educational goal for the future. The majority of the students stated that I want to go as far as I can to the level of education that they aim at. Nearly half of the students who express their perceptions of success as "Undecided" or "Failed" see themselves as the cause of underachievement, their friends as the cause of their underachievement. In addition, students expressed the most unsuccessful or unsuccessful courses in mathematics, English and Turkish, respectively. According to student opinions, the reasons for the underachievement are "I cannot succeed because of my brothers" and "I am not successful because of my health problems". A small proportion of the students in the survey showed their teachers as reasons for underachievement. Underachievement to connect students' underachievement to an external influence can be seen as an important issue in terms of overcoming the problem of underachievement

Bu araştırmanın amacı ortaokul öğrencilerinin başarısızlık nedenlerinin öğrenci görüşlerine göre değerlendirilmesidir. Araştırmanın verileri araştırmacılar tarafından alanyazın taramasına göre oluşturulan başarısızlık nedenleri anketi yardımıyla toplanmıştır. Araştırmanın bulgularından biri öğrencilerin geleceğe yönelik öğretim hedefi belirlemede zorlandıklarıdır. Öğrencilerin büyük çoğunluğu hedeflediği öğretim kademesini gidebildiğim yere kadar gitmek istiyorum olarak ifade etmiştir. Başarı algılarını “Kararsızım” veya “Başarısızım” şeklinde ifade eden öğrencilerin yaklaşık yarısı başarısızlık nedeni olarak kendilerini, arkadaşlarının başarısızlık nedeni olarak arkadaşlarını görmektedirler. Ayrıca öğrenciler sırasıyla en çok başarısız oldukları ya da çalıştıkları halde başaramadıkları dersi matematik, İngilizce ve Türkçe olarak ifade etmişlerdir. Öğrenci görüşlerine göre başarısızlık nedeni olarak öne çıkanlar “Kardeşlerim yüzünden başarılı olamıyorum” ve “Sağlık sorunlarım olduğundan başarılı olamıyorum” nedenleridir. Araştırma kapsamındaki öğrencilerin çok az bir bölümü başarısızlık nedeni olarak öğretmenlerini göstermişlerdir. Öğrencilerin başarısızlıklarını bir dış etkene bağlamamaları başarısızlık sorununun aşılması açısından önemli bir durum olarak gösterilebilir.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Başarısızlık; Öğrenci görüşleri; Ortaokul öğrencileri; Akademik başarı; Underachievement; Student opinions; Secondary school students; Academic achievement